IMPLEMENTASI KEBIJAKAN PENGELOLAAN USAHA PERTAMBANGAN RAKYAT: THE POLICY IMPLEMENTATION IN PEOPLE’S MINING MANAGEMENT - Zainudin; Murati, Ferra; Saptawartono; Kristianie, Yunitae; Tarigan, Rio Rivaldo; Saputra, Rafiq Aldi; Br Ginting, Elisa Alemina; Sista Dewi, Iqramina; Ariatama, Gerry; Yuliana Samosir, Sonia; Iqbal, Muhammad (JURNAL TEKNIK PERTAMBANGAN, 2023)
People's Mining is a permit to carry out mining business in a people's Mining area with a limited area and investment. People's Mining Activities are as follows: Metal Mineral Mining, Non-Metal Mineral Mining, Rock Mining. People's Mining Area (WPR) is part of the Mining Area (WP) where WP is part of the Legal Mining Area. According to data, WPR in Indonesia has a total area of 580,712 hectares with a total of 3,329 blocks. IPR data throughout Indonesia recorded at the Directorate General of Minerals and Coal as of November 2020 totaled 16 IPRs. This number is very minimal when compared to the number of WPR blocks and the total area of smallholder mining areas in Indonesia. This is the background for conducting research, namely the study of how to implement community mining business management policies. The method used in this study is a qualitative method in which data is sourced from journals and previous research to obtain data in the form of research on legal effectiveness which from the point of view of its form is evaluative research. Mining policies provide directions for the implementation of the Mining Law and its implementing regulations, bearing in mind that a regulation is more general in nature. So that the government and the people who carry out mining business activities have guidelines or instructions, how people's mining business activities are in accordance with mining regulations. Through this policy, the government provides benefits to miners but remains within the regulatory framework that governs them.  Keywords: People's mining,region, policy